KEPASTIAN HUKUM PEMBATALAN AKTA SEWA MENYEWA OLEH PENGADILAN TERKAIT WANPRESTASI OLEH PENYEWA DALAM PERJANJIAN SEWA MENYEWA - Syahwir Hafiz; Amelia Nur Widyanti; Furcony Putri Syakura3 (Bajang Institute, 2026)
A lease agreement executed in the form of a notarial deed, as regulated under Article 1548 of the Indonesian Civil Code, may be rescinded due to default as stipulated in Article 1243 of the Civil Code, with legal consequences pursuant to Articles 1266 and 1267 thereof, which in principle require formal recognition through a court decision. The issues examined in this study concern the legal consequences of the annulment of a deed by the court in relation to default committed by the lessee, and the legal certainty of such judicial annulment arising from the lessee’s default. The theoretical framework applied in this research consists of the theory of legal certainty as formulated by Jan Michiel Otto and the theory of legal consequences as developed by Soeroso. The research method used is normative juridical research, namely legal research based on library materials or secondary data, consisting of primary, secondary, and tertiary legal materials. The research approaches employed include the statutory approach, case approach, analytical approach, and conceptual approach. The collection of legal materials is carried out by identifying and inventorying positive legal norms, book literature, journals, and other legal sources. The analysis of legal materials is conducted through legal interpretation, namely grammatical interpretation and systematic interpretation, as well as methods of legal construction, including analogical construction and legal refinement. The findings of this research showed that the judicial annulment of a lease agreement due to the lessee’s default not only terminates the contractual relationship, but also gives rise to new legal consequences in the form of changes in the legal status of the parties, the affirmation of post-contractual rights and obligations, and the imposition of enforceable civil sanctions, such that legal certainty is genuinely achieved when the provisions of the Civil Code are applied consistently and judicial decisions are implemented concretely in accordance with the concept of realistic legal certainty